Perception of massage application among clinicians and parents in spastic cerebral palsy: Qualitative Study - Iqra Tul Hussain; Qurat Ul Ain; Misbah Waris, Misbah Waris (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the perceptions about traditional massage and its modified techniques among clinicians and families of the patients with spastic cerebral palsy. Method: The qualitative, cross-sectional study was conducted from November 2019 to August 2020 in Sialkot, Pakistan, after approval from the ethics review committee of Riphah College of Rehabilitation Sciences, Islamabad, and comprised neuro paediatricians and paediatricians in Group A, parents of children with spastic cerebral palsy aged 8-15 years in Group B, and musculoskeletal physiotherapists and orthopaedic manual physical therapists in Group C. The professionals in groups A and C had a minimum of 5-year paediatric experience in government and teaching hospitals. Data was collected using a semi-structured pilot-tested questionnaire. Qualitative approach and thematic code analysis was used to analyse the collected data. Results: Of the 26 subjects, 10(38.5%) were in Group A, 8(30.7%) in Group B and 8(30.7%) in Group C. Overall, there were 16(61.4%) males and 10(38.5%) females. Among the professionals, experience ranged 5-38 years in Group A, and 5-9 years in Group C. The identified themes were reforms in recommendations, and application of massage techniques, with the participants overwhelmingly favouring termination markers to prevent increase in hypertonicity in spastic cerebral palsy. Conclusion: Termination markers of massage should be considered in interventions to improve outcomes in children with spastic cerebral palsy. Key Words: Cerebral palsy, Massage therapy, Perception, Swiss massage, Spasticity.